1994
DOI: 10.1103/revmodphys.66.1481
|View full text |Cite
|
Sign up to set email alerts
|

Biological pattern formation: from basic mechanisms to complex structures

Abstract: The reliable development of highly complex organisms is an intriguing and fascinating problem. The genetic material is, as a rule, the same in each cell of an organism. How then do cells, under the influence of their common genes, produce spatial patterns' Simple models are discussed that describe the generation of patterns out of an initially nearly homogeneous state. They are based on nonlinear interactions of at least two chemicals and on their diffusion. The concepts of local autocatalysis and of long-rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
496
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 605 publications
(517 citation statements)
references
References 106 publications
(84 reference statements)
11
496
0
2
Order By: Relevance
“…This mechanism implies that R8s are chosen earlier than previously thought, during the initial process of induction. Unlike previous scenarios (8,9), the switch and template mechanism predicts that genetically identical tissue can readily sustain different patterns depending on initial conditions, as we verify experimentally.…”
mentioning
confidence: 56%
“…This mechanism implies that R8s are chosen earlier than previously thought, during the initial process of induction. Unlike previous scenarios (8,9), the switch and template mechanism predicts that genetically identical tissue can readily sustain different patterns depending on initial conditions, as we verify experimentally.…”
mentioning
confidence: 56%
“…This could explain why the symmetry is robustly kept when it is generated starting from a disk-like embryological structure, as in the case of the sea urchins. On the contrary, when the primordia grow starting from a symmetry breaking along a string-like one-dimensional structure, as in the case of leaf and flower initiation during plant growth [17], the final symmetry could not be controlled in an unique way. For instance, a single strawberry plant can produce flowers with a variable number of petals (see below).…”
Section: Discussionmentioning
confidence: 99%
“…The pattern with spots exhibiting hexagonal symmetry is ubiquitous in Turing models for biological morphogenesis [14,[17][18][19]. A weakly nonlinear theory based on corresponding amplitude equations has been recently developed to study the stability of this unavoidable hexagonal pattern [20].…”
Section: Discussionmentioning
confidence: 99%
“…An RD mechanism provides an effective solution to this problem. Many mathematical studies have shown that the RD system is able to account for most of the animal coat pattern (Murray, 1989;Koch and Meinhardt, 1994).…”
Section: Introductionmentioning
confidence: 99%